THE EFFECTIVENESS OF A CONSTRUCTIVIST TEACHING MODEL ON STUDENTS’ UNDERSTANDING OF PHOTOSYNTHESIS - Dolenc Orbanić, Nataša; Skribe Dimec, Darja; Cencič, Majda (Journal of Baltic science education, 2016)
Photosynthesis is one of the fundamental processes on Earth and it ranks among the most demanding science concepts for students, associated with a number of misconceptions. For improving students’ understanding and learning outcomes the constructivist approach has proven to be one of the most effective. In this research the constructivist teaching model of photosynthesis (CTMP) was designed and its effectiveness on students’ understanding was tested. Students (N=201) from Slovenian primary schools (aged 11–12 years) participated in the research. CTMP was used in the experimental group (EG), while the traditional teaching approach was used in the control group (CG). Students’ learning achievements were evaluated using the paper-and-pencil tests. The test items were classified into three groups based on Bloom’s taxonomy: (1) knowledge, (2) comprehension and application, and (3) analysis, synthesis, evaluation. Mann-Whitney U-test showed that the EG had better learning outcomes than the CG. Statistically significant differences were found at the highest cognitive level. The CTMP contributes to the improvement of teaching and learning of photosynthesis, fosters the development of higher-order thinking and offers opportunity for integration of the constructivist approach in science classes, which will help to increase the quality of acquired knowledge and to raise the level of scientific literacy of the population.